Doubly-Excited States of Beryllium-Like Ions with Screened Coulomb Potentials - Arijit Ghoshal (Atoms, 2018)
The screening effects of the interaction potentials on the lowest 1S doubly-excited states of beryllium-like ions were investigated by calculating the density of resonance states within the framework of the stabilization method. Two types of screened interaction potentials, namely static screened Coulomb potential and exponential cosine screened Coulomb potential, were taken into consideration. A model potential was used to describe the interaction between the core and outer electrons, and the Be-like ions were treated as being effectively three-body systems. Calculations were performed for Be and B+. It was possible to calculate the energy and width of one doubly-excited state of Be and four doubly-excited states of B+ lying above the 1s22p threshold. Significant changes were found to exist in the behaviour of the width with varying screening parameters. To the best of our knowledge, such an investigation on the doubly-excited states of Be-like ions under screened environments is the first reported calculation of this type in the literature.